Plane crash the forensics of aviation disasters - Bibel, G. D. (George D.); Hedges, Robert 1964- (Johns Hopkins University Press, 2018)
If you have ever wondered what goes through a pilot's mind as a flight takes a turn for the dangerous, what impact turbulence actually has on flight safety, or even just how the wonders of aeronautics work to keep passengers safe day in and out, Plane Crash will both fascinate and educate.